Self-Concept and Its Influence on Friendship Quality: A Study of Adolescent Girls in Specialized Educational Settings - Zanirah, Fairuz; Deasyanti; Suryaratri, Ratna Dyah; Akbar, Zarina; Ariyani, Mira; Maulana, Herdiyan (Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to analyze the influence of self-concept on the quality of friendships among female adolescents in an all-girls full-day school environment. The research employs a quantitative non-experimental design with a cross-sectional approach, utilizing simple linear regression analysis. The participants consist of female junior high school students attending a full-day school exclusively for girls in Bogor. The instruments used in this study include the Tennessee Self Concept Scale 2nd Edition (TSCS 2nd Edition) to measure self-concept and the Friendship Quality Scale (FQUA) to assess the quality of friendships. The regression results indicate a positive and significant correlation between self-concept and friendship quality (r = 0.424; p < 0.001), with self-concept contributing 18% of the variance in friendship quality. These findings suggest a significant influence of self-concept on the quality of friendships among female adolescents in the all-girls school setting.